Newton : A very short introduction - Rob Iliffe (Very short introductions, 158., 2007)
Newton: A Very Short Introduction introduces Newton's scientific studies in fields ranging from physics, astronomy, and mathematics, to alchemy. It also examines his controversial theological beliefs and his politics, and explores the forces that shaped his life. Although Newton's science was largely revered - his reputation reached near-immortal status with the publication of the Principia - theologically, his beliefs were very controversial. Newton's views on alchemy, mathematics, physics, and religion are shown to be the very different obsessions of an extremely complex man whose beliefs at the time dominated England's political, religious, and intellectual landscape.